PEMBERDAYAAN MASYARAKAT DESA PURWASARI MELALUI TEKNOLOGI SEX REVERSAL DAN PENGOLAHAN FILLET IKAN NILA OREOCHROMIS NILOTICUS - Wildan Nurussalam; Fajar Maulana; Bintang Lazuardi; Bulan Puspa Adamy; Mutia Amanda; Sundari Rahayu Ningsih; Namirah Fitri Ramadhani; Erwan Rusdiawan; M. Egi Fahlisya Aditya P; Noval Restuaji; Ammar Dzaky Maulana; Surya Baskara; Aisya Sonia Alamanda; Brandon Mustafa Hidayat; Nadia Cahyawati; Josua Daniel Manurung; Apriana Vinasyiam (Universitas Mataram, 2023)
Purwasari Village is a village that has great potential in the field of aquaculture. These potentials include ponds that have not been utilized optimally and water sources that are channeled from irrigation. In addition, the potential in the field of human resources in Purwasari Village with groups engaged in fisheries is still not maximized. The people of Purwasari Village have a high interest in aquaculture activities, but the lack of knowledge related to cultivation aspects is an obstacle to improving the quality of production. In addition, the slow growth of female tilapia caused by wild spawning causes an increase in feed costs which is one of the main limiting factors for cultivators. The purpose of the PPK Ormawa activity is to empower the Purwasari Village community through monosex tilapia cultivation and tilapia fillet processing in order to increase village profitability and community food security during the Covid-19 pandemic. This activity method is carried out in a hybrid way, offline activities are carried out for field surveys, counseling and controlling and online activities are carried out to hold online meetings between lecturers, presenters and village communities as well as evaluation of ongoing program activities. This activity succeeded in increasing the knowledge, skills, number of members of the target group and the responsibilities of each individual. Physical change indicators can be seen in the revitalization of ponds and the provision of hatchery, nursery and rearing pond infrastructure for monosex tilapia. The formation of the Women Farmers Group for processing tilapia fillets and increasing the number of members of the Millennial Tani Tani group.